New research opportunities in the earth sciences (National Academies Press, 2012)
"Identifies new and emerging research opportunities in the earth sciences over the next decade, including surface and deep earth processes and interdisciplinary research with fields such as ocean and atmospheric sciences, biology, engineering, computer science, and social and behavioral sciences. The report also identifies key instrumentation and facilities needed to support these new and emerging research opportunities. The report describes opportunities for increased cooperation in these new and emerging areas between EAR and other government agency programs, industry, and international programs, and suggests new ways that EAR can help train the next generation of Earth scientists, support young investigators, and increase the participation of underrepresented groups in the field." --Publisher's web site.